An approach to the Quechua of Santa: structural characterization and sociolinguistic diagnosis - Quesada Castillo, Félix (2012)
First of all, this study characterizes the structural system of the Quechua dialect spoken in the province of Santa (Ancash, Peru)), and focuses on the phonological level, the nominal and verbal morphology, as well as on aspects of its syntax (the structure of the phrase and nominal subordination). From the phonological and morphological features, it is established that this variety originates from the province of Huaylas and, that form there, it spreaded out towards the west up to its present location, in the communities in the districts of Jimbe and Moro. Secondly, we apply the methodology of sociolinguistics (through a survey) and that of ethnography of communication (the scientific procedure of the participating observation) in order to get a revealing diagnosis of the Quechua speaking community. Based on the application of this method, it is possible to determine that the variety in question goes through the phenomenon of linguistic switching from Quechua to Spanish; wich is motivated by its diglosic relation with Spanish (the socially dominant language). The evidences of the switching phenomenon form Quechua to Spanish are the restriction in its use in community and family settings, and the influence of Spanish model on the evolution of this Quechua dialect. This scenerio allows us to conclude that we are facing a variety of Quechua which is in risk of extinction.